ARACEOUS AND NONARACEOUS HOSTS OF TARO FEATHERY MOSAIC DISEASE - Palomar, Manuel K.; Duatin, Joji Y.; Palermo, Victoria G. (Annals of Tropical Research, 1984)
Six plant species belonging to Araceae and one species of Solanaceae were infected with taro feathery mosaic disease. Typhonium trilobatum (Linn.) Schott, Dieffenbachia maculata, Dieffenbachia sp., and Datura metel Blanco were highly susceptible while Xanthosoma sp. was moderately susceptible. Caladium bicolor (Avit.) Vent showed stunting and leaf distortion while Cyrtosperma merkussii (Linn.) Schott was the only species which showed latent infection. Dieffenbachia spp. had an average incubation period of 4.5 days followed by D. metel with 7.8 days; T. trilobatum, 13.5 days; Xanthosoma sp., 14.4 days; C. bicolor, 17.6 days and C. merkussii, 14 days. Back-inoculation to taro showed the positive presence of taro feathery mosaic in these plants.